Factors that lead to organizational politics amongst administrative staff in UiTM City Campus Malacca / Khairuldin Anwar - Anwar, Khairuldin (Faculty of Administrative Science and Policy Studies, 2011)
Organizational politics is a natural part of organizational life since organizations are made up of different interests that need to be aligned. Organizational politics has been discussed in earnest in the literature over the last two decades. The concept of organizational politics and the perceptions of organizational politics in the work place evolved during the 1990’s and are considered to be a primary component in contemporary business practices. Organizations that are driven by unhealthy levels of political behavior suffer from lowered employee organizational commitment, job satisfaction, and performance as well as higher levels of job stress, anxiety and depression. The purposes of this research study is to identify the most influential factors that lead to organizational politics practices, identify the effects of practicing organizational politics towards work performance and identify the solution in overcoming the negatives effects of organizational politics practices amongst administrative staff in UiTM City Campus Malacca.